STRATEGI PENGELOLAAN DALAM MENINGKATKAN DAYA SAING PARIWISATA BERBASIS MASYARAKAT PADA OBJEK WISATA BENGKAUNG LOMBOK BARAT - Kaysi, Afif Dzul; Purwata, I Ketut; Bratayasa, I Wayan (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to find out how the local community is involved in managing of tourism at Bengkaung tourism objects, Batu Layar Sub-District, West Lombok Regency. This study used a qualitative research method with a descriptive qualitative approach. The data used in this study were obtained directly using the interview method with research informants, namely the Village Government, Pokdarwis Chairmen, Communities and Tourists. Data analysis techniques were carried out using qualitative data analysis techniques, including data reduction, data presentation, and verification/drawing conclusions and SWOT analysis to formulate the right strategy in the management and development of tourism at Bengkaung tourism objects. Testing the validity of the data was carried out using the triangulation method. Based on the data analysis that has been carried out, the results show that tourism management at the Bengkaung tourist attraction has been carried out with the concept of community based tourism (CBT). The forms of community involvement in community-based tourism management at Bengkaung tourism objects, namely community involvement in managing tourist objects, community involvement in protecting the environment of tourist objects, and community involvement in efforts to gain profit. SWOT analysis in the management and development of tourism at Bengkaung tourism objects produces four alternative strategies, namely SO strategy, WO strategy, ST strategy and WT strategy.